The Role of HbA1C for Diagnosis of Type-2 Diabetes Mellitus - A Review (Faridpur Medical College Journal, 2016)
For many years, the diagnosis of diabetes has been made through the laboratory- based measurement of fasting or random blood glucose levels or using OGTT. In the case of diabetes, the major outcome of interest is long term micro vascular complications for which a large body of data has been accumulated leading to the endorsement of HbA1C for diagnosis in many countries worldwide, with some variations in cut-offs and testing strategies.Faridpur Med. Coll. J. Jan 2016;11(1): 30-32